Towards a conceptual framework on the categorization of stereotypical perceptions in accounting. Issue 1 (October 2015) - Richardson, Peter; Dellaportas, Steven; Perera, Luckmika; Richardson, Ben
Abstract: The stereotypical image of the profession is poor with accountants appearing in the popular media as either the object of satire or the criminally inclined expert who deceives the public for self-gain. Extant research on the portrayal of the stereotypic accountant is limited in two ways: (1) existing research assumes a unitary concept by inferring a dominant image when the accountant stereotype is multifaceted; and (2) it is unclear from existing research whether the dominant image results from perceived character traits or the duties undertaken by accountants. This paper relies on qualitative methods of data analysis to unpack the elements that underpin stereotypical images in accounting to develop a framework of external perceptions that distinguishes one image from another. The framework is constructed on two broad criteria that comprise accountants (personality traits and physical characteristics) and accounting (task functionality). The interplay of these two criteria creates four subtypes representing positive (Scorekeeper and Guardian) and negative (Beancounter and Entrepreneur) interpretations of the two basic categorizations: bookkeeper and business professional. Further analysis revealed four primary dimensions (Ethics and Sociable, Skill and Service) that underlie the construction of the subtypes. In general, the 'Scorekeeper' rates more highly than the 'Beancounter' on 'Ethics and Sociable' and the 'Guardian' rates more highly than the 'Entrepreneur' on 'Ethics'. Accounting researchers and the profession could benefit from understanding how stereotypical perceptions are constructed and managed.